2010
DOI: 10.1002/lapl.201010037
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 1.7-μJ pulses at 1.55 μm by a self-mode-locked all-fiber laser with a kilometers-long linear-ringcavity

Abstract: We report on the record-high pulse energy of nearly 1.7 μJ obtained directly from a self-mode-locked all-fiber erbium laser with a linear-ring cavity owing its extreme elongation up to several kilometers. Specially selected telecommunication fibers, providing large normal net cavity dispersion in the vicinity of 1.55 μm, have been used for this purpose. Along with compensation for polarization instability in the longer linear arm of the cavity, such approach has ensured stable wavebreaking-free mode-locked las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…They demonstrated the possibility of passive mode locking in long cavities due to saturable absorbers, such as single-wall carbon nanotubes [25,40,41], semiconductor saturable absorber mirrors [42][43][44], and non-linear optical loop mirrors [45]. It was experimentally and theoretically confirmed that passively mode-locked fiber master oscillators give rise to a broad variety of generation regimes in different cavity configurations [46][47][48][49][50][51][52][53], including generation of single and multiple pulses over a cavity round-trip, pulses with various duration, envelope shape, and spectrum width. The results of Refs [30,52] show that in ultra-long lasers, there is high probability of generating double-scale partially coherent pulses, whereas ''normal'' (single-scale) pulses with a smooth temporal optical phase shape and large chirp become difficult to obtain.…”
Section: Ultra-long Mode-locked Fiber Lasers: Discussionmentioning
confidence: 92%
“…They demonstrated the possibility of passive mode locking in long cavities due to saturable absorbers, such as single-wall carbon nanotubes [25,40,41], semiconductor saturable absorber mirrors [42][43][44], and non-linear optical loop mirrors [45]. It was experimentally and theoretically confirmed that passively mode-locked fiber master oscillators give rise to a broad variety of generation regimes in different cavity configurations [46][47][48][49][50][51][52][53], including generation of single and multiple pulses over a cavity round-trip, pulses with various duration, envelope shape, and spectrum width. The results of Refs [30,52] show that in ultra-long lasers, there is high probability of generating double-scale partially coherent pulses, whereas ''normal'' (single-scale) pulses with a smooth temporal optical phase shape and large chirp become difficult to obtain.…”
Section: Ultra-long Mode-locked Fiber Lasers: Discussionmentioning
confidence: 92%
“…New results obtained in the experiments (Kobtsev et al, 2008c) with relatively high energy of pulses directly in a passively mode-locked laser stimulated further investigations in this area Zhang et al, 2009;Lin et al, 2011;Song et al, 2011;Ai et al, 2011;Kobtsev et al, 2009;Senoo et al, 2010;Kelleher et al, 2009;L. Chen et al, 2009;Nyushkov et al, 2010;Kobtsev et al, 2010a;Ivanenko et al, 2010). In particular, demonstrated experimentally in (Kelleher et al, 2009) were 1.7-ns-long pulses with a giant chirp generated in 1,2-km-long fibre laser mode-locked due to nanotube-based saturable absorber.…”
Section: Review Of Recent Progress In Mode-locked Fibre Lasers With Hmentioning
confidence: 89%
“…Such comparative complication of the optical trains for the generation of high-energy pulses justifies the interest in the intra-cavity methods for increasing the pulse energy without any additional amplification stages. A method based on an increase in the cavity length was successfully employed in (Kobtsev et al, 2008a,c;Kong et al, 2010;Nyushkov et al, 2010;Kobtsev et al, 2010a, b, c). However, the experiments show that the stability of ultra-long lasers with nonlinear polarisation evolution (NPE) mode locking is lower compared to the stability of short lasers on the time scale of the round trip of the cavity and on longer time scales (about one hour).…”
Section: Prospects and Limitationsmentioning
confidence: 99%
“…In lasers of this type, the pulse energy of several microjoules was demonstrated [1,8,11] without using any traditional methods such as Q-switching or cavity dumping techniques. In lasers using saturable absorbers, e.g.…”
Section: Introductionmentioning
confidence: 98%